The combination of CXCL9, CXCL10 and CXCL11 levels during primary HIV infection predicts HIV disease progression - Yin, Xiaowan (J Transl Med, 2019)
BACKGROUND: Chemokines are small chemotactic cytokines involved in inflammation, cell migration, and immune regulation in both physiological and pathological contexts. Here, we investigated the profile of chemokines during primary HIV infection (PHI). METHODS: Fifty-four participants with blood samples before and during HIV infection and clinical information available were selected from an HIV-negative man who have sex with men (MSM) prospective cohort. Thirty chemokines and 10 cytokines were measured pre- and post-HIV infection in the same individuals using a Bio-Plex Pro™ Human Chemokine Panel. RESULTS: Levels of 18 chemokines/cytokines changed significantly during PHI relative to pre-HIV infection levels; 14 were up-regulated and 4 down-regulated. Among them, CXCL9, CXCL10, and CXCL11 were the most prominently raised. Levels of CXCL9 and CXCL10 were much higher in the high-set point group (log viral load (lgVL) ≥ 4.5) than those in the low-set point group (lgVL < 4.5) and levels of CXCL9, CXCL10, and CXCL11 were higher in the low-CD4(+) T-cell count group (CD4(+) T-cell count ≥ 500). A formula to predict HIV disease progression using a combination panel comprising CXCL9, CXCL10, and CXCL11 was developed, where risk score = 0.007 × CXCL9 + 0.004 × CXCL10 − 0.033 × CXCL11 − 1.724, with risk score values higher than the cutoff threshold (0.5211) indicating more rapid HIV disease progression. CONCLUSIONS: A panel of plasma CXCL9, CXCL10, and CXCL11 measured during primary HIV-1 infection could predict long-term HIV disease prognosis in an MSM group and has potential as a novel biomarker in the clinic.